Dried Bombay Duck or Bombil - Mumbai Archive Project Team (Jio Institute, 2024)
Bombay duck is one of the most popular fish used to make dried fish. Other species include ribbon fish (pictured here), also known as vaala or belt fish; mackerel, locally known as bangda; sardines, known as tarli or pedvey in Marathi; and prawns, known as jhinga.